Students’ Perception on Speaking Practice at Koplo English Club Community - Sabdi, Sabdi; Muliawati, Ida; Ayouni, Nour (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2024)
This research aimed to find out and describe the students’ perception on speaking practice at Warkop English Orchestra (KOPLO) English Club Community. The researchers used descriptive quantitative method in which the data were gained from questionnaire consisting of 10 close-ended questions. There were 22 members of the club selected to be the respondents of the study. Data were analyzed by using a five-point of Likert Scale, mean score, weighted mean score, combined mean score and score interval. The result presented that the highest mean score is 4.09 as in question number 11. The members frequently use vocabulary that they have encountered when they speak English. The lowest score falls to number 10 with a score of 3.27 which means that students are not really fluent without stutter when speaking English. Based on the combined mean score, the respondents show their good perception of speaking practice at KOPLO which obtained the mean score 3.62. It means community plays a very important role and has a positive effect on students who join it, one of which is being able to increase student vocabulary. However, students still have deficiencies in fluency.